Influence of seed priming treatments on germination parameters improvement of pea (Pisum sativum L.) - مجید تولیت ابوالحسنی; رضا توکل افشاری; محمدرضا جهانسوز; فرزاد نجفی; حسنعلی نقدی بادی (علوم و فناوری بذر ایران)
In order to evaluate the effect of different seed priming treatments on germination parameters improvement in Pisumsativum L.a factorial experiment was conducted in completely randomized design with four replications in seed science and technology laboratory of agriculture faculty, Shahrekord University in 2013. The experimental factors were consisted as priming types (osmopriming, halopriming and hydropriming) and priming times (12, 24 and 36 hours). Results showedthat different priming treatments had significant effect on radicle length, shoot length, shoot dry weight, radicle dry weight, germination percentage, germination rate, relative germination, vigor indexesIn addition to,priming times had significant effect in all measured traits except germination rate Themaximum radicle length, germination percentage, relative germination and vigor index I achieved with concentration of 1.1 MPa PEG and 24 hours. The maximum shoot length and germination rate obtained with distilled water treatment, 24 hours and concentration of 0.7 MPa PEG, 24 hours, respectively. The lowest amount of all measured traits was observed in concentration 1.2 MPa KNO3 with 36 hours. In conclusion, the high doses of PEGwith 24 hoursis suitable for germination improvement of pea seeds.